2020
DOI: 10.1021/acs.jpcb.0c06304
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Dynamics Studies on the Effect of Surface Roughness and Surface Tension on the Thermodynamics and Dynamics of Hydronium Ion Transfer Across the Liquid/Liquid Interface

Abstract: Molecular dynamics simulations are used to examine the effect of surface roughness and surface tension on the transfer of the classical hydronium ion (H3O+) across the water/1,2-dichloroethane interface. Free energy of transfer, hydration structure, and dynamics as a function of the ion location along the interface normal are calculated with six different values of a control parameter whose variation modifies the surface tension without impacting the bulk properties of the two solvents. Transfer of the classic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 57 publications
0
5
0
Order By: Relevance
“…The ion can be stabilized at the interface by a nearly complete hydration shell. The water molecules in the hydration shell are free to rapidly exchange with other nearby water molecules ( 57 ). Only when the ion is further pushed into the oil phase does this process become less likely and the free energy rises rapidly.…”
Section: Resultsmentioning
confidence: 99%
“…The ion can be stabilized at the interface by a nearly complete hydration shell. The water molecules in the hydration shell are free to rapidly exchange with other nearby water molecules ( 57 ). Only when the ion is further pushed into the oil phase does this process become less likely and the free energy rises rapidly.…”
Section: Resultsmentioning
confidence: 99%
“…Both theory and surface selective spectroscopies have been used to study liquid–liquid interfaces. For example, vibrational sum-frequency generation (VSFG) has revealed details on surface structure by monitoring changes in the OH-stretching region of water. The Richmond group has published an extensive study using VSFG, of the CCl 4 –water interface in the presence of various surfactants, biomolecules, and ions.…”
mentioning
confidence: 99%
“…When the ion is transferred to the organic phase, the ion can be accompanied by its hydration shell water molecules as shown in Figure c. Such molecular details are important for the optimization of the phase-transfer catalyst as previous experimental and theoretical studies suggested that the hydration state of the ion can strongly affect the reactivity. ,, …”
Section: Introductionmentioning
confidence: 99%
“…25,30,31 Free-energy change of the ion transfer ΔF, which is the minimum amount of work required to transfer the ion from one phase to another, is one of the key thermodynamic quantities obtained in both experimental and computational studies. [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27]32,33 By MD simulations, Dang 21 studied the freeenergy change of Cl − transfer across the water−dichloromethane interface using polarizable models. They found that the free-energy change calculated from their MD simulations, 14(±2) kcal/mol, is in reasonable quantitative agreement with the experimental value, 10(±1) kcal/mol.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation